2019
DOI: 10.1017/jfm.2019.258
|View full text |Cite
|
Sign up to set email alerts
|

Splashing of droplets impacting superhydrophobic substrates

Abstract: A drop of radius $R$ of a liquid of density $\unicode[STIX]{x1D70C}$, viscosity $\unicode[STIX]{x1D707}$ and interfacial tension coefficient $\unicode[STIX]{x1D70E}$ impacting a superhydrophobic substrate at a velocity $V$ keeps its integrity and spreads over the solid for $V<V_{c}$ or splashes, disintegrating into tiny droplets violently ejected radially outwards for $V\geqslant V_{c}$, with $V_{c}$ the critical velocity for splashing. In contrast with the case of drop impact onto a partially wetting subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…The splashing criterion within this theory is defined as β = √ F L /(2σ ). The agreement of this latter theory with multiple experiments has influenced recent modifications that consider the drop impact on heated (Staat et al 2015), moving (Hao & Green 2017), inclined or hydrophobic (Quintero, Riboux & Gordillo 2019) surfaces.…”
Section: Introductionmentioning
confidence: 84%
“…The splashing criterion within this theory is defined as β = √ F L /(2σ ). The agreement of this latter theory with multiple experiments has influenced recent modifications that consider the drop impact on heated (Staat et al 2015), moving (Hao & Green 2017), inclined or hydrophobic (Quintero, Riboux & Gordillo 2019) surfaces.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, figures 6 and 7 also show that the droplet disintegrates more irregularly when increases. The first row, highlighted in black, corresponds to the case of a smooth glass substrate, the second row, highlighted in blue, corresponds to experiments done with a SH coating (Quintero et al 2019) whereas the rest of the cases correspond to SC sandpapers. The splash cases are highlighted in pink.…”
Section: Experimental Set-up and Phenomenologymentioning
confidence: 99%
“…Motivated by the observations above, in the remainder of this contribution, three different theoretical frameworks will be used to predict, in an approximate way, the splash transition on rough substrates: the one for smooth partially wetting substrates deduced in Riboux & Gordillo (2014) and will be employed here to describe the splash transition in the case We ε 1 and the rim wets the rough substrate. Moreover, a new result will be derived to describe the splash of drops impacting on wetting substrates when We ε 1 whereas the results in Quintero et al (2019) will be used to predict the value of the critical Weber number when the rim does not wet the solid. The similitudes between the present experimental results and those previously reported for smooth or SH coatings are further supported by the experimental evidence depicted for the case of water drops in figure 10, where it is shown that, in analogy with SH substrates, air pockets are entrapped between the expanding liquid film and the solid.…”
Section: Experimental Set-up and Phenomenologymentioning
confidence: 99%
“…Recently, drop impact on engineered microscale structures has been known to exhibit asymmetric spreading (11) and retraction (4) and a pancake-shaped rebouncing (12), finally leading to the rapid drop detachment with a significant decrease in the contact time (4,12). However, the role of microscale structures during drop impact was underestimated since most studies have focused on drop impacts at low speeds (4,5,13,14), much lower than real raindrop impact speeds in natural events.…”
mentioning
confidence: 99%